Clinical and Genetic Spectra of Inherited Liver Disease in Children in China - Youhong Fang; Jindan Yu; Jingan Lou; Kerong Peng; Hong Zhao; Jie Chen (Frontiers Media S.A., 2021)
Background: Children presenting with chronic liver disease or acute liver failure often have an underlying genetic disorder. The aim of this study was to analyze the clinical and genetic spectra of inherited liver disease in children in a tertiary hospital.Methods: A total of 172 patients were classified into three groups according to their clinical presentation: cholestasis (Group A), liver enzyme elevation (Group B), and hepato/splenomegaly (Group C). Next-generation sequencing (NGS) was performed on all patients recruited in this study. The genotypic and phenotypic spectra of disease in these patients were reviewed.Results: The median age at enrollment of the 172 patients was 12.0 months (IQR: 4.9, 42.5 months), with 52.3% males and 47.7% females. The overall diagnostic rate was 55.8% (96/172) in this group. The diagnostic rates of whole-exome sequencing (WES) and targeted gene panel sequencing (TGPS) were 47.2% and 62.0%, respectively (no significant difference, p = 0.054). We identified 25 genes related to different phenotypes, including 46 novel disease-related pathogenic mutations. The diagnostic rates in the three groups were 46.0% (29/63), 48.6% (34/70), and 84.6% (33/39). ATP7B, SLC25A13, and G6PC were the top three genes related to monogenic liver disease in this study.Conclusion: WES and TGPS show similar diagnostic rates in the diagnosis of monogenic liver disease. NGS has an important role in the diagnosis of monogenetic liver disease and can provide more precise medical treatment and predict the prognosis of these diseases.